PENGGUNAAN MEDIA AUDIO DALAM PEMBELAJARAN MENYIMAK DONGENG PADA SEKOLAH DASAR (STUDI EKSPERIMEN KUASI SISWA KELAS V SD NEGERI 67 PEKANBARU) - Melliani Jasprila; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the teacher is still tied to the monotonous method is less open to the renewal, thus inhibiting the students to be active and creative causes low quality of students. Utilization of audio media is expected to influence in improving learning listening. This research is a research with quasi experimental method with nonequivalent control group design. The purpose of this study is to determine the effect of the use of media audo on learning to listen to class V fairy tales and to find out the difference in enhancement of listening ability between the experimental class and control in learning listening tale using audio media. This research was conducted at SD 67 Negeri Pekanbaru with VA class as control class treated with lecture method and class V B as experimental class treated with audio media usage. The results showed that there is an influence of audio media in learning to listen to fairy tales and there is a difference in the improvement of listening ability between the experimental class and control class using the audio media. In the experimental class there is an increase in learning listening from the average of 64,3 pretest test to 87,88 in the posttest test with average gain of 0.66 medium category. While the control class had an increase of 65.76 in the pretest test to 74.80 in the final test (postest) with an average gain of 0.24 low category. In this research, it is known that there is influence of the use of audio media is very strong to the learning of listening fairy tales of students of class V SD 67 Country 67 Pekanbaru in experimental class with coefficient of determination 0,90. Audio media influence learning listening tale by 90% while 10% of listening listening learning influenced other factors not discussed in this research. Thus, the audio media have a very strong effect on the learning of listening tale with the improvement of better listening ability than the application of lecture method.Key Word: Audio Media, Listening, The Tale